The behavior of permeable paving properties using different materials in their compositions: a review of the literature - Prado, Amanda Rafaely Monte do; Pessoa Neto, Amaury Gouveia; Muniz, Débora Vieira; Silva, Simone Rosa da; Rabbani, Emilia Rahnemay Kohlman (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
This systematic review addresses the behavior of the properties of permeable pavements with different materials in their compositions, with the objective of raising the state of the art of this area of study in a worldwide scenario. For this, the largest possible number of papers available was listed, according to the eligibility and quality criteria, detected in the Engineering Village, Scopus and Science Direct databases. After reading the titles and abstracts of all identified papers, 28 were chosen associated with the theme, of which 15 were included for the review. This result made it possible to demonstrate that the compensatory technique of permeable pavement is used in several parts of the world, presenting satisfactory results. Several studies presented in this work aimed to replace or even introduce other types of materials in the composition of permeable pavements, seeking to achieve better results in their properties, especially in mechanical and hydraulic.